Foundations of digital signal processing : theory, algorithms and hardware design - Gaydecki, Patrick (Institution of Electrical Engineers, 2004)
An introductory text, this book covers the basic theoretical, algorithmic and realtime aspects of digital signal processing (DSP).
Keywords: Signal processing -- Digital techniques.; elektronické knihy; electronic books